Examining the Role of Spatial Changes in Bimodal and Uni-Modal To-Be-Ignored Stimuli and How They Affect Short-Term Memory Processes - Marsja, Erik; Marsh, John E.; Hansson, Patrik; Neely, Gregory (Frontiers in Psychology, 2019)
Abstract This study examines the potential vulnerability of short-term memory processes to distraction by spatial changes within to-be-ignored bimodal, vibratory, and auditory stimuli. Participants were asked to recall sequences of serially presented digits or locations of dots while being exposed to to-be-ignored stimuli. On unexpected occasions, the bimodal to-be-ignored sequence, vibratory to-be-ignored sequence, or auditory to-be-ignored sequence changed their spatial origin from one side of the body (e.g., ear and arm, arm only, ear only) to the other. It was expected that the bimodal stimuli would make the spatial change more salient compared to that of the uni-modal stimuli and that this, in turn, would yield an increase in distraction of serial short-term memory in both the verbal and spatial domains. Our results support this assumption as a disruptive effect of the spatial deviant was only observed when presented within the bimodal to-be-ignored sequence: uni-modal to-be-ignored sequences, whether vibratory: or auditory, had no impact on either verbal or spatial short-term memory. Implications for models of attention capture, and the potential special attention capturing role of bimodal stimuli are discussed.